Poisoning of Mitochondrial Topoisomerase I by Lamellarin D - Khiati, Salim (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Lamellarin D (Lam-D) is a hexacyclic pyrole alkaloid isolated from marine invertebrates, whose biologic properties have been attributed to mitochondrial targeting. Mitochondria contain their own DNA (mtDNA), and the only specific mitochondrial topoisomerase in vertebrates is mitochondrial topoisomerase I (Top1mt). Here, we show that Top1mt is a direct mitochondrial target of Lam-D. In vitro Lam-D traps Top1mt and induces Top1mt cleavage complexes (Top1mtcc). Using single-molecule analyses, we also show that Lam-D slows down supercoil relaxation of Top1mt and strongly inhibits Top1mt religation in contrast to the inefficacy of camptothecin on Top1mt. In living cells, we show that Lam-D accumulates rapidly inside mitochondria, induces cellular Top1mtcc, and leads to mtDNA damage. This study provides evidence that Top1mt is a direct mitochondrial target of Lam-D and suggests that developing Top1mt inhibitors represents a novel strategy for targeting mitochondrial DNA.